2013
DOI: 10.1159/000347071
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging-Based versus Computed Tomography-Based Thrombolysis in Acute Ischemic Stroke: Comparison of Safety and Efficacy within a Cohort Study

Abstract: Background: In acute ischemic stroke, brain imaging is mandatory in the decision whether to perform intravenous thrombolysis with recombinant tissue plasminogen activator. The most widespread used imaging modality to exclude intracranial hemorrhage is plain computed tomography (CT). However, there is an ongoing debate whether the information provided by magnetic resonance imaging (MRI) could improve the selection of patients for thrombolysis. We investigated whether the choice of imaging modality (MRI vs. CT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…We have previously shown that patients undergoing MRI before thrombolysis have less cardiac comorbidities and lower rates of sICH and 7-day mortality compared with patients receiving CT imaging before thrombolysis. 3 However, this applies to patients with and without CCM, and this bias should not affect the relative risk for sICH and PH between both compared groups. Another limitation is the retrospective and monocentric design of our study, possibly limiting the extent to which our results could be generalized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that patients undergoing MRI before thrombolysis have less cardiac comorbidities and lower rates of sICH and 7-day mortality compared with patients receiving CT imaging before thrombolysis. 3 However, this applies to patients with and without CCM, and this bias should not affect the relative risk for sICH and PH between both compared groups. Another limitation is the retrospective and monocentric design of our study, possibly limiting the extent to which our results could be generalized.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline characteristics of our single-center thrombolysis register have been described before. 3 Patients with additional thrombectomy or intra-arterial thrombolysis were not included because of potentially different risk for ICH. Diagnosis of CCM was based on MRI (3 T, Siemens, TimTrio) and confirmed by a neuroradiologist (J.B. Fiebach).…”
Section: Study Population and Data Acquisitionmentioning
confidence: 99%
“…Some authors suggested that MRI-based thrombolysis was related to an improved safety compared to CT-based treatment [30,31] , whereas others argued that using CT-scan allows limiting the delays between the onset of symptoms and the thrombolysis [32,33] . Indeed, ultrafast door-to-needle time (less than 25 min) has been reported by selective centers using CT [34,35] .…”
Section: Discussionmentioning
confidence: 99%
“…Selection bias includes the single-center setting and patients' ability to undergo MRI. 32 Because of the observational and nonrandomized design, we cannot provide evidence whether the overall benefit of IVT is attenuated in patients with multiple CMBs. Furthermore, we did not control for volume of pretreatment diffusion-weighted imaging lesion, which was shown to be a relevant MRI predictor of sICH.…”
Section: Strokementioning
confidence: 97%